Critical life cycle inventory for aluminum die casting: A lightweight-vehicle manufacturing enabling technology. (15th December 2021) - Liu, Weipeng; Peng, Tao; Kishita, Yusuke; Umeda, Yasushi; Tang, Renzhong; Tang, Wangchujun; Hu, Luoke
Highlights: High-pressure/high-vacuum/semi-solid aluminum die casting are considered. Resource and emission flows analysis is conducted with onsite data collection. A critical and configurable inventory of aluminum die casting is complemented. High-vacuum/semi-solid die casting are energy conservation enabling-technologies. Several favorable energy conservation & emission reduction measures are offered. Abstract: Driven by the target of carbon neutrality, the vehicle industry is striving to implement energy conservation and emission reduction (ECER). Aluminum (Al) alloy, which is an effective ECER solution, is the dominant lightweight material for vehicles. Nearly 60% of vehicle Al components are produced by die casting (DC), which can achieve a 30–50% weight reduction. However, Al DC is highly energy intensive and environmentally polluting. It is necessary to assess the life cycle ECER effects of vehicle Al die castings (DCs). However, the existing research weakly supports this assessment, particularly in the manufacturing stage. In addition, the effective implementation of ECER for Al DC is crucial but lacks attractive measures. To bridge these gaps, a system boundary is first defined, including three scenarios: high-pressure DC, high-vacuum DC, and semi-solid DC. A detailed process division and data description are introduced. Then, a thorough inventory analysis is conducted with an in-depth investigation and on-site data collection. Finally, a more representative and configurable inventory compared to existing studies and life cycle assessment databases is provided. It is revealed that the energy consumption in the manufacture of structural DCs is nearly 80% larger than that of box-type DCs. High-vacuum DC and semi-solid DC can reduce the total energy by 3.5% and 9.9%, respectively. Several targeted ECER measures are proposed with intensive analyses and surveys. In addition, the sensitivity of specific Al DCs to the developed inventory is discussed, as are the suggested measures considering energy generation.